2001
DOI: 10.1021/ie000957a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Oxidative Degradation of Aqueous Monoethanolamine in a Flue Gas Treating Unit

Abstract: An investigation of the kinetics of the oxidative degradation of aqueous monoethanolamine (MEA) was conducted in a 300-mL autoclave in the temperature range 393−443 K and MEA concentration range 2−11 kmol/m3 at 241−345 kPa O2 pressure (i.e., O2 concentration range). The results show that MEA oxidative degradation depends on both the O2 and the initial MEA concentrations, as well as the temperature, according to the intrinsic kinetic model −r MEA = 2.5 × 105e-(66 288.9/ RT )[MEA][O2]1.5. This work represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 3 publications
2
47
0
Order By: Relevance
“…Thermal degradation has been studied by several research groups over a long period of time (Davis and Rochelle, 2009;Eide-Haugmo, 2011;Lepaumier et al, 2009a;Polderman et al, 1955) while oxidative degradation has received increased attention the last decade (Goff and Rochelle, 2004;Lepaumier et al, 2009;Rooney et al, 1998;Supap et al, 2001) as it was discovered that oxidative degradation compounds are the main products under real plant conditions (da Silva et al, 2012;Lepaumier et al, 2011a;Strazisar et al, 2003). Increased insight into the degradation mechanisms, through knowledge of stoichiometry, kinetics, and chemical pathways, may result in methods for eliminating or strongly reducing degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal degradation has been studied by several research groups over a long period of time (Davis and Rochelle, 2009;Eide-Haugmo, 2011;Lepaumier et al, 2009a;Polderman et al, 1955) while oxidative degradation has received increased attention the last decade (Goff and Rochelle, 2004;Lepaumier et al, 2009;Rooney et al, 1998;Supap et al, 2001) as it was discovered that oxidative degradation compounds are the main products under real plant conditions (da Silva et al, 2012;Lepaumier et al, 2011a;Strazisar et al, 2003). Increased insight into the degradation mechanisms, through knowledge of stoichiometry, kinetics, and chemical pathways, may result in methods for eliminating or strongly reducing degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Either the amine loss was studied working in a closed-batch reactor at elevated temperatures and oxygen pressures (Lepaumier et al, 2009;Supap et al, 2001;Wang and Jens, 2011), or in an open-batch reactor at 55 °C where the CO2-loaded amine solution would be sparged with a wet gas blend of CO2 and air (da Silva et al, 2012;Goff and Rochelle, 2004;Lepaumier et al, 2011a;Lepaumier et al, 2011b). Lately there has been increased focus on the effect of temperature swing under industrial operation and an integrated solvent degradation apparatus (ISDA) was developed where the solvent is exposed to both oxidative and thermal degradation conditions in a single system (Closmann and Rochelle, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MEA has strong interaction with oxygen (Supap et al, 2001(Supap et al, , 2006Bello and Idem, 2005;Chi and Rochelle, 2002;Goff andRochelle, 2004, 2006;Sexton and Rochelle, 2009;Bedell, 2009Bedell, , 2011Bedell et al, 2011;Lepaumier et al, 2009b, c). Working closer to the absorption conditions, Sexton and Rochelle (2009) have shown that ammonia is the major by-product in the gas phase and is a good indicator of MEA oxidative degradation.…”
Section: Potential Interactions With the Solvent And The Incinerator mentioning
confidence: 99%
“…Increased attention on oxidative degradation was seen after pilot plant samples showed high degree of similarity to degradation compounds found in oxidative degradation experiments (da Silva et al, 2012;Lepaumier et al, 2011a;Strazisar et al, 2003). The oxidative degradation experiments reported have been performed in variations of two setups, either in a closed-batch reactor at elevated temperature and oxygen pressure (Lepaumier et al, 2009b;Supap et al, 2001;Wang and Jens, 2011) or in an open-batch reactor at 55 °C, where the solution would be sparged with a wet gas blend of CO2 and O2/air (da Silva et al, 2012;Goff and Rochelle, 2004;Lepaumier et al, 2011b;Sexton and Rochelle, 2011). Lately, also the temperature swing The present paper describes results from oxidative degradation experiments on five amines and two amino acids in a laboratory scale closed setup at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%